FISHERY POTENTIAL ALONG THE INDIAN COASTAL WATERS BETWEEN PORBANDAR AND RATNAGIRI - GAJBHIYE, S. N.; MEHTA, PRATIK; MUSTAFA, S.; NAIR, VIJAYALAKSHMI R. (Journal of Indian Fisheries Association, 2015)
As part of the ongoing marine pollution monitoring programme thecoastal stretch between Porbandar and Ratnagiri was considered toassess the fishery potential. Regular experimental trawling was doneoff Porbandar, Veraval, Diu, Hazira, Daman, Bassein, Bombay, Murudand Ratnagiri at a depth range of 5-25 m during 1988 to 1992. Thecatch rate varied from 1.2 to 225 kglh (av.20~3 kg/h). Zonewise maximumcatch (av.56.8 kg/h) was observed off Ratnagiri followed by offPorbandar (av.30.1 kg/h), off Bombay (av.23.9 kg/h) and off Murud(av.l9.8 kg/h). The area between Hazira and Daman was poor in fishcatch. In general, the catch rate showed a fluctuating trend during theperiod of observation. Among the hundred species identified from thecollections the most common species were Coilia dussumieri, Johniusglaucus, Scoliodon lati,caudus, Lepturacanthus savala, Harpadonnehereus, Sardinella longiceps, Pampus sp. and Congresox sp. Thecommunity structure and species assemblage at different zones arediscussed in detail.